Review of Current Immunologic Therapies for Hidradenitis Suppurativa - Shanmugam, Victoria K. (Int J Rheumatol, 2017)
Hidradenitis suppurativa (HS) is a chronic, recurrent, inflammatory disease of apocrine gland-bearing skin which affects approximately 1–4% of the population. The disease is more common in women and patients of African American descent and approximately one-third of patients report a family history. Obesity and smoking are known risk factors, but associations with other immune disorders, especially inflammatory bowel disease, are also recognized. The pathogenesis of HS is poorly understood and host innate or adaptive immune response, defective keratinocyte function, and the microbial environment in the hair follicle and apocrine gland have all been postulated to play a role in disease activity. While surgical interventions can be helpful to reduce disease burden, there is a high recurrence rate. Increasingly, data supports targeted immune therapy for HS, and longitudinal studies suggest benefit from these agents, both when used alone and as an adjunct to surgical treatments. The purpose of this review is to outline the current data supporting use of targeted immune therapy in HS management.